A case study of enterprise risk management implementation in Malaysian construction companies - Mustapha, Mazlina; Adnan, Amirah (EconJournals, 2015)
Enterprise Risk Management (ERM) is claimed as among the key elements in the internal control components, which help the organizations to ensure that principal risks are monitored and managed well within the organizational structure. Implementing ERM in organizations would help to put the process of monitoring, reviewing and identification of risks in a better perspective. This study attempts to explore the ERM implementation in Malaysian construction companies. This sector is chosen as it is claimed that ERM can help construction companies make appropriate and accurate decisions in planning and construction of projects. In addition, this study is conducted to assist and improve ERM implementation of a small construction company. A comparison is conducted between this small company to a bigger construction company, which has implemented ERM for a number of years in an effort to assist the former to improve its implementation. Interviews were conducted to obtain the data for the study. Top management, risk owners, and employees of both companies were interviewed. The interview results were analyzed and presented to the smaller company. Among others, the results suggest that the awareness and understanding of ERM concept by employees is the main factor in ensuring a successful ERM implementation because the employees will be the first to experience such risks in their day-to-day operations. Participation from all level of employees, especially the commitment from the top management is crucial to ensure its successful implementation. In addition, continuous maintenance activities such as follow up monitoring and maintenance of a risk management exercises are important in managing risks effectively.